Advances in sulodexide-based long-term anticoagulation for a myasthenia gravis patient with giant thymoma - Liu, Zhou; Zhang, Liang; Peng, Wei; Chen, Qianqian; Hou, Yanguang; Zhan, Liying; Li, Guang (Frontiers in Pharmacology, 2025)
This case report describes a geriatric male patient with myasthenia gravis (MG) secondary to giant thymoma, presenting with progressive muscle weakness and ptosis. The diagnosis of MG was confirmed through pathology, imaging, and laboratory evaluations. Considering the significant surgical risks associated with the giant thymoma, adjuvant chemotherapy was initiated. Unfortunately, 2 weeks following chemotherapy, the patient developed acute respiratory failure and sudden loss of consciousness. Emergency endotracheal intubation was performed, and he was then transferred to the intensive care unit (ICU) and treated with immunoglobulin, plasmapheresis, prednisone, and pyridostigmine. During ICU hospitalization, the patient developed severe lower limb edema accompanied by increased skin temperature, particularly on the left side. Ultrasound imaging confirmed extensive thrombosis in the left iliac and femoral veins, with thrombosis involving 50%–67% of the venous lumen. To prevent the risk of pulmonary embolism (PE), an inferior vena cava filter was implanted, and low-molecular weight heparin (LMWH) was prescribed for anticoagulation. Unfortunately, the patient later experienced intermittent melena and heparin-induced thrombocytopenia (HIT), with hemoglobin levels decreasing to 55 g/L and platelet counts decreasing to 57 × 109/L. Given the adverse events associated with LMWH, sulodexide (SDX) was substituted as a novel anticoagulant with multiple benefits, including reduced thrombosis and bleeding risk, anti-inflammatory effects, and vascular endothelium protection. SDX demonstrated excellent efficacy and safety, with no adverse effects observed during the 3-year follow-up period. In conclusion, SDX should be considered an ideal potential option for long-term anticoagulation in patients with complex conditions such as MG with both thrombotic and bleeding risks.